Crop rotation with no-till methods in cotton production of Uzbekistan - Botir Khaitov; Kholik Allanov (Eurasian Journal of Soil Science, 2014)
Many soils of Uzbekistan have low water and nutrient holding capacity because of their sandy texture, low organic matter concentrations and degradation caused by long years of cotton monoculture. Conservation tillage production systems have the potential to increase the productivity of these soils by increasing soil humus and nitrogen content. As practiced conservation tillage helped to lessen N leaching losses, holding more of these elements within the topsoil as well as increase crop productivity. Conventional tillage cotton/wheat/maize crop rotation has resulted very low humus and nitrogen content in soil by degreasing crop yield. Therefore, the effects of tillage, and crop rotation were examined on growth and yield of crops in three cotton-based rotation systems, (i) cotton/wheat/maize, (ii) cotton/wheat/sorghum and (iii) cotton/wheat/soybean, in Tashkent region in middle east of Uzbekistan. This obtained result suggests that no tillage with inserting legumes in crop rotation is able to improve soil quality and plant productivity.